Distortion of Local Architecture Identity A comparative study for the rebuilding process of the buildings on Sabunkaran street - Abdullah, Wrya S.; Shari, Aako N. (Sulaimani Journal for Engineering Sciences, 2019)
The historic urban regions and architecture are more than mere materials remained, they are central to how the community see themselves and their architecture identity as individuals, communities and as a nation. In a transient and rapidly changing world, interests are in; “What the local identity of the community architecture is? and how the original identity of the local architecture could be kept during the new rebuilding process in the historic and old regions of the city?” Architecture identity is therefore; an inheritance that helps to define the future architecture by inspiring new ideas and providing solutions to the problems that the community face in the age of globalisation. In this way, historic and old urban regions of the city greatly show the original architecture identity which helps the community to distinguish their architecture from others. This paper studies the distortion of local architecture identity on Sabunkaran Street as a part of the old region and city centre in Sulaimaneyah city in means of style, building materials and architectural elements as a result of the new rebuilding process. The distortion of building materials, styles and elements for the new rebuilt process are compared to the context of the region without sub-categorizing each part to specific items. This paper makes a comparative study for the architecture on Sabunkaran Street to show how the local architecture identity of the old region has the risk of distortion as a result of the new rebuilding process done in the last decades. This study aims to keep the local architecture identity of the old urban regions to show the future generations their original architecture identity. The study hypotheses that; new rebuilding process achieved by the individual owners in old urban spots lead to the distortion of local architecture identity if it is not monitored by specialized local authorities.
Keywords: Identity; local architecture; local architecture identity; distortion